Effectiveness of Humanistic Approach Assisted by Learning Media to Increase Motivation Student Learning in MTs Darul Huffaz Pesawaran - Hernadi Hernadi; Rangga Firdaus; Nurlaksona Eko Rusmianto (UNDIKMA, 2023)
Learning motivation is an absolute requirement for learning and plays an important role in providing passion or enthusiasm in learning. Motivation to learn is not only a driving force to achieve good results but contains efforts to achieve learning goals in motivation contained a desire that activates, moves, channels and directs attitudes and behavior in individuals. The humanistic approach views humans as subjects who are free to determine the direction of their lives. Humans are responsible for their own lives and for the lives of others. This research aims to explain the humanistic approach assisted by learning media to increase students' learning motivation.This research uses the (SLR) method. regarding research methods: